Job Crafting On Work Engagement: Person Job Fit As Mediation Variable - Yuliani, Vanessa; Trinanda, Okki (Human Resource Management Studies, 2023)
This study aims to analyze: (1) The effect of Job Crafting on Work Engagement in employees of the Maritime Affairs and Fisheries Office of West Sumatra Province. (2) The effect of Job Crafting on Person-Job Fit in employees of the Office of Maritime Affairs and Fisheries of West Sumatra Province. (3) The effect of Person-Job Fit on Work Engagement in employees of the West Sumatra Province Maritime Affairs and Fisheries Office. (4) The effect of Job Crafting on Work Engagement mediated by Person-Job Fit for employees of the West Sumatra Maritime Affairs and Fisheries Service. This research is a causal research. The population in this study were all employees of the Office of Maritime Affairs and Fisheries of West Sumatra Province, totaling 92 employees. While the number of samples used in this study was determined by using total sampling so that the sample is the same as the population, which is 92 people. The analysis technique used is SmartPLS 4 software. The results of this study indicate that: (1) Job Crafting has a positive and significant effect on Work Engagement for employees of the Maritime Affairs and Fisheries Office of West Sumatra Province. (2) Job Crafting has a positive and significant effect on Person-Job Fit for employees of the Maritime Affairs and Fisheries Office of West Sumatra Province. (3) Person-Job Fit has a positive and significant effect on Work Engagement for employees of the Office of Maritime Affairs and Fisheries of West Sumatra Province. (4) Job Crafting has a positive and significant effect on Work Engagement mediated by Person-Job Fit for employees of the Maritime Affairs and Fisheries Office of West Sumatra Province.